(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
The article discusses the linguistic sign and proposes a definition that is based on a usage-based view of language and includes all communication systems, also closed ones like the traffic lights. Content, expression and signs as wholes are discussed separately, and the linguistic sign is compared to “semiotic” signs. The main claims are: 1) Reference is primarily mental and part of the content. 2) A mentalistic definition of signs is incompatible with a usage-based view. The expression isphysical, in language as in usage.3) Neither arbitrariness, linearitynor double articulation are necessary qualities of signs. 4) Spoken, written and gestural languages are sign systems of their own, not manifestations of an abstract language with no particular expression. 5) Only minimal signs (morphemes) consist of expression and content. Complex signs consist of (smaller)signs. 6) The linguistic sign isa category of its own, not a subtype of “semiotic” signs.